The synthesis of carbon nanostructures from tea plant wastes - Guler, Omer; Boyrazli, Mustafa; Basgoz, Oykum; Bostanci, Bayram (Taylor & Francis Ltd, 2017)
Tea wastes are rich in carbon, nitrogen and potassium but poor in phosphorus, which signifies that they can also be used to reduce metal oxides after they are carbonised. The tea wastes were carbonised at the first stage. The sample, which was put into a ladle with screw cap, was carbonised in a muffle furnace at 400, 500, 600, 700 and 800 degrees C for 30, 60, 90, 120, 240, 360, 720 and 1440 min. It was determined that carbon and sulphur contents of the sample carbonised at 800 degrees C for 1440 min were 94.68 and 0.05%, respectively. Calorific value of the same sample was 8652 cal g(-1). It was found that with increasing temperature, carbon ratio of the carbonised samples increased and their sulphur ratio decreased from 0.39 to 0.05%. The carbonised structure was subjected to the milling process as the second stage. In the milling process, particle size of the carbon-rich sample was brought into nano size and the structure acquired the energy, required for the third stage. The amorphous carbon structure obtained after the milling process was subjected to annealing process at 1400 degrees C as the third stage. As a result of these processes, carbon nanotubes (CNTs), carbon nano-onion structures and amorphous carbon structures were determined in the structure.
Keywords: Tea wastes; carbonisation; carbon nanotubes; nano-onion; ball milling; mechano-thermal process